THE IMPACT OF INTERNAL AUDIT QUALITY ON FINANCIAL PERFORMANCE OF MSMES IN KANO STATE, NIGERIA - Nura Musa; Sagir Lawal; Felix Karma (CV Visionary Raya Sakti, 2026)
Research Objectives: To examine the effect of internal audit quality (IAQ) on the financial performance of selected Micro, Small, and Medium Enterprises (MSMEs) in Kano State, Nigeria, specifically investigating the influence of auditor independence, competence, objectivity, audit scope, stakeholder engagement, and continuous improvement practices. Design/ Methodology / Approach Research: A quantitative research design rooted in the positivist paradigm. Primary data were collected via structured questionnaires administered to 50 respondents across five purposively selected MSMEs. Data analysis employed descriptive statistics and multiple regression analysis using SPSS and Stata software. Research Results: Internal audit quality has a significant positive effect on financial performance (measured by ROA). All IAQ dimensions (independence, competence, objectivity, scope, stakeholder engagement, and continuous improvement) positively contribute, with auditor competence and continuous improvement practices being the most influential factors. The model demonstrates strong explanatory power (R² = 82.1%). ​ Implications of Research Results: MSMEs should invest in developing competent and independent internal audit units, regularly update audit procedures, and integrate audit feedback into strategic decision-making. This strengthens transparency, accountability, and optimal financial management, thereby enhancing performance and sustainability.